Case Report: Endoscope-Assisted Bilateral Nasal Leech Retrieval in a Dog - Singh, Manpreet; Kumar, Amit; Kumar, Adarsh; Tyagi, Som P.; Wadhawan, Rishu (Frontiers in Veterinary Science, 2022)
A non-descript male dog was presented with symptoms such as chronic recurrent epistaxis, sneezing and episodes of nasal leech infestation from past 3 months. The dog was subjected to basic clinical examination, hemato-biochemistry test and radiographic examination before rhinoscopy. Rhinoscopy was performed with Karl Storz 5 mm video-otoscope under general anaesthesia. Leech infestation in the nasal cavity was found to be the cause of the epistaxis under rhinoscopic examination. The endoscopic guided retrieval of leech from both the nostrils was done with help of grasping forceps without any major complication. The video-otoscope guided retrieval of nasal leech was quite convenient and also provide the exact localization of the nasal leech.